Redox and essential metal status in the brain of Wistar rats acutely exposed to a cadmium and lead mixture - Javorac Dragana; Đorđević Aleksandra Buha; Anđelković Milena; Tatović Simona; Baralić Katarina; Antonijević Evica; Kotur-Stevuljević Jelena; Đukić-Ćosić Danijela; Antonijević Biljana; Bulat Zorica (Arhiv za Higijenu Rada i Toksikologiju, 2020)
Most Pb and Cd neurotoxicity studies investigate exposure to either of the toxic metals alone, while data on co-exposure are scarce. The aim of our study was to fill that gap by investigating acute combined effects of Pb and Cd on redox and essential metal status in the brain of Wistar rats. Animals were randomised in four groups of six to eight rats, which received 15 or 30 mg/kg of Cd, 150 mg/kg of Pb, or 150 mg/kg of Pb + 15 mg/kg of Cd by gavage. The fifth, control, group received distilled water only. Co-treatment with Pb and Cd induced significant increase in malondialdehyde (MDA) and thiobarbituric acid-reactive substances (TBARS) compared to control and groups receiving either metal alone. This is of special importance, as MDA presence in the brain has been implicated in many neurodegenerative disorders. The groups did not significantly differ in Zn, Cu, Mn, and Fe brain levels. Our findings highlight the importance of metal mixture studies. Neurotoxicity assessments of single chemicals do not provide a real insight into exposure to mixtures in real life. Further research should look into interactions between these metals to reveal complex molecular mechanisms of their neurotoxicity.